SIKAP APATISME MASYARAKAT DALAM PEMBERANTASAN KORUPSI DAN PATOLOGI BIROKRASI MENUJU PELAYANAN PUBLIK PRIMA (Studi di Kab. Malang, Kota Malang, Kota Batu) - Dody Setyawan (REFORMASI, 2012)
Corruption has become a serious problem in Indonesia since it spread to entire fields and sectors of community widely, systematically, and well organized. Therefore, it causes community has apathetic attitude to all corruption types, either conventional corruption (damaging nation finance) or non-conventional corruption (slowly in serving, escape from captivity, selfish, etc.), result in the public service done is not maximum. This research used qualitative method with descriptive approach through observation, interview, and documentation in collecting data. Data analysis used was interactive data analysis model developed by Miles and Hubeman (1992) covers data reduction process, data presentation, and conclusion. The conclusions of this research done are: 1)the community is extremely apathetic since the reality in removing corruption happened in bad way; 2) the effort in removing corruption in Malang city still becomes an issue of group and class (LSM and several people), it has not become the enemy of Malang city’s community yet; 3)the service has been good enough (the standard of service is available for each institution), however it has not been maximum yet in its execution; 4) to get a good public service, there should be a change of the way of thinking of people having capacity in bureaucracy.